Bydlení Satalice, přínosy prefabrikace bytového domu - Didunyk, Maxim; Maxim Didunyk (České vysoké učení technické v Praze, 2024)
Obsahem této diplomové práce je architektonický návrh souboru bytových domů v Praze Satalicích. Návrh řešení a hmotová kompozice vychází z předdiplomního projektu, který řešil urbanistický návrh zástavby bývalého brownfieldu u nádraží. Diplomový projekt rozpracovává část území ve větším detailu. Cílem práce je ověřit možnosti spojení malometrážních bytů a společných komunitních prostor. Navržené objekty využívají nosné dřevěné konstrukce a modulární systém výstavby.

The content of this diploma thesis is an architectural design of apartment buildings in Prague Satalice. The proposal solution and material composition is based on the pre-diploma project, which dealt with the urban design of the former brownfield development near the railway station. The diploma project elaborates part of the area in more detail. The aim of the work is to verify the possibilities of combining small flats and common community spaces. The proposed buildings use load-bearing wooden structures and a modular construction system.
Housing Satalice, the benefits of prefabrication of an apartment building
Keywords: bytový dům; modulární architektura; dřevostavba; apartment house; modular architecture; timber structure